The Association of Serum Testosterone Levels With Recurrence and Mortality After Acute Ischemic Stroke in Males. Issue 3 (20th May 2019) - Ho, Chen-Hsun; Wu, Chia-Chang; Lee, Mei-Ching; Huang, Pai-Hao; Chen, Jen-Tse; Liu, Shih-Ping; Liao, Pin-Wen
The current study aimed to investigate whether low testosterone predicted the recurrence and clinical outcomes after acute ischemic stroke (AIS) in males. From June 2015 through August 2017, the study prospectively enrolled 110 male AIS patients. All received detailed evaluations at admission and were followed for at least 1 year. The cumulative incidence, overall survival, length of hospital stay, and the percentage of previous stroke were compared between subjects with testosterone <440 ng/dl and >440 ng/dl. The median age was 62 years (range, 35–93 years). The median serum testosterone at admission was 438 [203] ng/dl (range, 44–816 ng/dl); 55 patients (50%) had testosterone <440 ng/dl and were considered as low testosterone. The median follow-up was 23 months. During the period, 12 recurrences and 10 deaths occurred. The 1-year and 3-year cumulative recurrence rate were 8.3% and 11.9%, respectively; the 1-year and 3-year overall survival were 96.3% and 84.6%, respectively. The cumulative recurrence rates were similar between the two testosterone groups (log-rank test, p = .88). Low testosterone was associated with poor survival with marginal significance (log-rank test, p = .079). Men with low testosterone had a higher percentage of previous stroke (29.1% versus 12.7%, p = .035). The mean lengths of hospital stay were similar between the two testosterone groups (16.6 ± 15.8 days versus 14.0 ± 10.6, p = .31). Total testosterone at admission fails to predict stroke recurrence. However, men with low testosterone at admission are more likely to have previous stroke and may have a higher all-cause mortality rate after AIS.